2008
DOI: 10.1007/s00464-008-9990-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for the curative treatment of rectal cancer: results of a Chinese three-center case–control study

Abstract: The findings showed that LR for rectal cancer was safe and effective, resulting in faster recovery and a similar complication rate compared with OR. Conversion did not alter the patients' outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
(48 reference statements)
4
18
0
Order By: Relevance
“…Importantly, we also have shown similar overall survival, cancer-specific survival, disease free-survival, and local and distant recurrence rates between the two groups. Regarding short-term results such as reduced length of hospital stay, and similar overall morbidity and mortality, our results were consistent with prior publications comparing open and laparoscopic approach in colorectal surgery, especially the decreased rates of wound infection for LS compared with OS [3,4,6,[10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, we also have shown similar overall survival, cancer-specific survival, disease free-survival, and local and distant recurrence rates between the two groups. Regarding short-term results such as reduced length of hospital stay, and similar overall morbidity and mortality, our results were consistent with prior publications comparing open and laparoscopic approach in colorectal surgery, especially the decreased rates of wound infection for LS compared with OS [3,4,6,[10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…The conversion rate in this study (18.6%) was comparable to conversion rates reported in previous studies assessing LS for rectal cancer, which range from 2.9 to 21.9% [6][7][8][9][12][13][14]. Our high conversion rate can be attributed to the fact that all patients who underwent the procedure over a prolonged period were reviewed, thus including patients who underwent surgery during the learning curve for laparoscopic resections.…”
Section: Discussionsupporting
confidence: 83%
“…At the moment, we have a number of noncontrolled series [10][11][12][13][14][15][16] and controlled nonrandomized cases at our disposal [2,[17][18][19][20], leading us to believe that this technique also could be used in the future by centers with less experience. Debate can now move from the technical problems to the oncologic difficulties because the advantages of the mini-invasive approach in the postoperative period have already been demonstrated [21], and because findings also have demonstrated that sexual and urinary sequelae are not more serious than those connected with the open approach [19], as it seemed some years ago [22]. In our series, the conversion rate was particularly low (4.6%).…”
Section: Discussionmentioning
confidence: 80%
“…In our series, the conversion rate was particularly low (4.6%). In the greatest number of papers, the conversion rate is about 15%, reaching 18% for the initial experience [3,17], and varying from 7 to 10% for more recent experience [11,18,21] to 18% [23]. Only in the Strasbourg series was a conversion rate of 3% reported [8].…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, in a randomized study of only colon cancer patients, it was observed that longer operative times (142X118 minutes) were significantly associated with laparoscopic surgery (p<0,001) 20 . In regards to rectal cancer, a case-control study from three centers also found significantly longer operative times (180X150 minutes) among patients treated laparoscopically (p<0,001) 9 . A 2008 metaanalysis of 25 randomized studies 30 reinforced the findings of longer operative times in laparoscopic colorectal surgery for CRC.…”
Section: Discussionmentioning
confidence: 99%